2016
DOI: 10.1080/14728222.2017.1271415
|View full text |Cite
|
Sign up to set email alerts
|

MERS-CoV spike protein: a key target for antivirals

Abstract: Introduction The continual Middle East respiratory syndrome (MERS) threat highlights the importance of developing effective antiviral therapeutics to prevent and treat MERS coronavirus (MERS-CoV) infection. A surface spike (S) protein guides MERS-CoV entry into host cells by binding to cellular receptor dipeptidyl peptidase-4 (DPP4), followed by fusion between virus and host cell membranes. MERS-CoV S protein represents a key target for developing therapeutics to block viral entry and inhibit membrane fusion. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
303
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(307 citation statements)
references
References 99 publications
2
303
0
2
Order By: Relevance
“…The RBDs of SARS-CoV and MERS-CoV contain multiple conformation-dependent neutralizing epitopes that induce more potent neutralizing antibodies and protective efficacy against SARS-CoV and MERS-CoV infections, respectively, than other regions in S protein [5,8,9]. Modification of MERS-CoV S-RBD amino acid residues based on the structure design could improve its protection against MERS-CoV infection [9], suggesting that 2019-nCoV S-RBD or modified S-RBD of other coronavirus may be applied for developing 2019-nCoV vaccines.…”
mentioning
confidence: 99%
“…The RBDs of SARS-CoV and MERS-CoV contain multiple conformation-dependent neutralizing epitopes that induce more potent neutralizing antibodies and protective efficacy against SARS-CoV and MERS-CoV infections, respectively, than other regions in S protein [5,8,9]. Modification of MERS-CoV S-RBD amino acid residues based on the structure design could improve its protection against MERS-CoV infection [9], suggesting that 2019-nCoV S-RBD or modified S-RBD of other coronavirus may be applied for developing 2019-nCoV vaccines.…”
mentioning
confidence: 99%
“…The baculovirus expression system presented in this study may serve as an effective vector to construct virus-like particles for vaccine production. Although this system expressed H6HA1-His protein and secreted into the medium efficiently, we found that it was not successful in producing the spike protein (S1) of Middle East respiratory syndrome coronavirus (Du et al, 2017). The secretion of S1 was poor, even though it was expressed at adequate level in the cell (data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…The S1 subunit contains the receptor binding domain, and the S2 subunit is required for the membrane fusion of MERS-CoV. Therefore, the S protein is one of the targets for the development of MERS-CoV therapeutics (Du et al, 2017). Some neutralizing antibodies have been developed against the receptor-binding domain of S protein, which blocks the interaction of S protein with it is coexpressed with the E or N protein in insect cells and mammalian cells (Mortola and Roy, 2004;Siu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%